2023
DOI: 10.3390/gels9020119
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-Assisted Glycosylation with Glucose on the Functional and Structural Properties of Fish Gelatin

Abstract: The effects of ultrasound-assisted glycosylation (UG) with glucose (GLU) on the emulsifying properties, foaming properties, gelling properties, and structural properties of fish gelatin (FG) were investigated. It was shown that UG with high power and a long duration facilitated the Maillard reaction through the reduction of the free amino acid contents. UG significantly improved the emulsifying ability index and foaming capacity of FG whilst decreasing the gel strength. Rheological analysis showed that UG modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Tyrosine and phenylalanine in gelatin are the main fluorescent substances, and fluorescence analysis can reflect the minor changes in the tertiary structure of protein [ 26 , 27 ]. According to Figure 2 , the peak of FG-TG at 303 nm is higher than that of the original FG, and the fluorescence intensity significantly increases.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosine and phenylalanine in gelatin are the main fluorescent substances, and fluorescence analysis can reflect the minor changes in the tertiary structure of protein [ 26 , 27 ]. According to Figure 2 , the peak of FG-TG at 303 nm is higher than that of the original FG, and the fluorescence intensity significantly increases.…”
Section: Resultsmentioning
confidence: 99%
“…Glycosylation is an effective chemical method for protein modification, which mainly involves the covalent binding of ε-amino groups in protein molecules with carbonyl groups in reducing sugars to generate protein-polysaccharide adducts, thus changing the functional properties (emulsifying, foaming) of proteins [16]. Studies have shown that glycosylation can alter the functional properties of FG, especially for improving interfacial properties [9,17,18].…”
Section: Introductionmentioning
confidence: 99%